2008
DOI: 10.1177/0265407507086810
|View full text |Cite
|
Sign up to set email alerts
|

Cultural differences in intimacy: The influence of gender-role ideology and individualism—collectivism

Abstract: Two studies examined emotional intimacy in European Canadian and Chinese Canadian dating relationships. Cultural differences in gender-role ideology and individualism—collectivism were hypothesized to differentially contribute to self-disclosure and responsiveness, and in turn, intimacy. Study 1 revealed that Chinese Canadians' lower intimacy relative to European Canadians was mediated by their greater gender-role traditionalism but not by their individualism or collectivism. Study 2 further linked greater gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(80 citation statements)
references
References 59 publications
5
73
0
2
Order By: Relevance
“…Their behaviour can be explained by the hybridity of Chinese and western cultural values in Hong Kong society, which encourage Hong Kong citizens to be more aware of their individual rights and interests. This is in line with the results of recent research on the narrowing differences between Chinese and westerners on the perceptions of intimacy and connectedness with significant others (Han, 2002;Marshall, 2008;Tang & Dion, 1999). However, this does not mean that adolescent females would not unconsciously integrate the Chinese cultural values and gender stereotypes into their sexual behaviour and contraception practice (So & Cheung, 2005;To & Chu, 2009).…”
Section: Discussionsupporting
confidence: 90%
“…Their behaviour can be explained by the hybridity of Chinese and western cultural values in Hong Kong society, which encourage Hong Kong citizens to be more aware of their individual rights and interests. This is in line with the results of recent research on the narrowing differences between Chinese and westerners on the perceptions of intimacy and connectedness with significant others (Han, 2002;Marshall, 2008;Tang & Dion, 1999). However, this does not mean that adolescent females would not unconsciously integrate the Chinese cultural values and gender stereotypes into their sexual behaviour and contraception practice (So & Cheung, 2005;To & Chu, 2009).…”
Section: Discussionsupporting
confidence: 90%
“…It is noteworthy that Korean participants in the current study tended to perceive their relationships as less serious (''friends'' or ''casually dating'') than did American counterparts (''seriously dating''). Therefore, it seems that the lower scores on the current variables for Koreans reflect their tendency to avoid expressing intimate feelings or to underestimate them, which is consistent with previous findings that the expression of intimacy is more common in individualistic cultures than in collectivistic (Argyle et al, 1986;Marshall, 2008). Thus, Koreans might not engage in networking behaviors such as talking about their romantic relationships to their friends and family not because they are afraid of friends' or family's opinions but because they are not used to those activities related to intimacy.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, as no significant effect for sexual communication when experiencing physical violence was found for either men or women, this could possibly be explained from a cultural perspective on intimacy. It has been suggested that people in intimate relationships with more traditional gender roles are less likely to self-disclose on sexual matters (Marshall, 2008). Accordingly, it seems reasonable to assume that physical IPV experiences do not influence the extent to which IPV victims discuss their sexual wishes with their intimate partner.…”
Section: Impact Of Ipv Victimization On Ethnic Minorities' Well-beingmentioning
confidence: 99%